2007
DOI: 10.1016/j.virusres.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

A second RGD motif in the 1D capsid protein of a SAT1 type foot-and-mouth disease virus field isolate is not essential for attachment to target cells

Abstract: The amino acid sequence motif Arg-Gly-Asp (RGD), located in the surface-exposed βG-βH loop of the 1D protein of different serotypes and subtypes of foot-and-mouth disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The RGD motif is a known participant in the interaction of a number of ligands with cell receptors from the integrin superfamily (8). Residues of the RGD motif, as well as RGDassociated regions, have previously been shown to influence the activity of a number of enveloped and nonenveloped viruses (4,10,11,13,15,17,21,27,36,42,44,47,49,50,52,56). Moreover, as evidence of the importance of this region, a 10-mer DENV-2 synthetic peptide sequence that overlapped the flavivirus Mut-5-like region (i.e., flavivirus amino acid residues at the Mut-5 positions) inhibited the binding of a DENV-2 domain III envelope protein to mosquito but not mammalian cells, indicating that this region has more specificity for insect cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…The RGD motif is a known participant in the interaction of a number of ligands with cell receptors from the integrin superfamily (8). Residues of the RGD motif, as well as RGDassociated regions, have previously been shown to influence the activity of a number of enveloped and nonenveloped viruses (4,10,11,13,15,17,21,27,36,42,44,47,49,50,52,56). Moreover, as evidence of the importance of this region, a 10-mer DENV-2 synthetic peptide sequence that overlapped the flavivirus Mut-5-like region (i.e., flavivirus amino acid residues at the Mut-5 positions) inhibited the binding of a DENV-2 domain III envelope protein to mosquito but not mammalian cells, indicating that this region has more specificity for insect cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…Baby hamster kidney-21 cells (BHK-21, ATCC CCL-10) were maintained and propagated in Eagle's basal medium (BME; Life Technologies) as described previously (27) MAb isolation. Monoclonal antibodies (MAbs) were prepared by inoculating BALB/c mice with a blend of inactivated and purified 146S particles of SAT1/Kenya (KEN)/11/2005, SAT/2/ZIM/5/81, and SAT3/ ZIM/4/81.…”
Section: Methodsmentioning
confidence: 99%
“…The introduction of specific mutations into the cloned genomes of viruses has allowed the manipulation of the biological prop-erties of field and laboratory strains and presents a promising avenue for the design of safe and effective vaccines [28][29][30]. We have structurally-engineered recombinant SAT viruses, containing desirable antigenic determinants and cell adaptation phenotypes [28,31,32] providing the proof-of-concept to rationally design viruses with the desired biological properties of a good vaccine strain. Several studies have shown that inter-serotype chimeric vaccines successfully induce protective immune responses and protect FMD host species against live virus challenge [26,30,33].…”
Section: Introductionmentioning
confidence: 99%